KEPATUHAN IBU BALITA BERKUNJUNG KE POSYANDU DI DESA KARANGREJO KECAMATAN WONOSALAM KABUPATEN DEMAK - Susilowati, Endang (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Posyandu (Integrated Services Post) is basic health activities conducted by and for public society that is led by health worker to provide basic health services in order to reduce the number of maternal and neonatal death. The purpose of it is to promote society to manage and organise Posyandu optimally. However, in fact, people have not yet taken benefits from it and conducted Posyandu activity regularly every month. In Demak district, the number of active Posyandu is 617 posts out of 47,276 Posyandu. The objective of this research is to describe the compliance of mother to take her children to Integrated Services Post (Posyandu) in Karangrejo village, Wonosalam subdistrict, Demak district. The type of this research is descriptive study, with cross sectional approach. The population is a group of mothers who have under-five children in Karangrejo village, Wonosalam subistrict, Demak district, which is 78 mothers. Samples were taken using probability sampling technique, particularly cluster sampling. The instrument used is a questionnaire. The result of the research is the majority of respondents less than 30 years old which is 54 mothers (69%), with low education level (elementary and junior high school) which is 65 mothers (83℅), and 56 mothers (72℅) were compliant to take their children to Posyandu. Therefore, we need to give more information to mothers in order to take her children to Posyandu. Keywords: compliance, Posyandu (Integrated Services Post)